A new species of Sparsorythus Sroka & Soldán, 2008 (Ephemeroptera: Tricorythidae) from Western Ghats, Southern India - Muthukatturaja, Marimuthu; Balasubramanian, Chellaiah (Zootaxa, 2021)
A little stout crawler mayfly Sparsorythus nanjangudensis sp. nov., is described based on nymphs and male adult from Western Ghats, southern India. The new species is differentiated from all known species on the basis of the extended anterolateral margin of pronotum, absence of subapical teeth on claws and wing pads reaching abdominal segment III. Distribution and ecological notes are provided for the new species.